Dinamika Kurikulum di Indonesia - M. Asri (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2017)
Education does not have a standard reference, which covers access for revision by the authorities. Because education continues to grow along with the rolling times. Therefore, all matters relating to education also do not have a standard reference, including educational curriculum. The curriculum is one of the important elements that has a role to advance education in Indonesia, in accordance with the ideals of the constitution. Curriculum changes are not taboo for education in developed countries of the world (such as Japan, Finlandia, USA, etc.). Basically the dynamics of curriculum in Indonesia aims to make education in Indonesia able to compete with the developed countries in the world.